2020
DOI: 10.1038/s41398-020-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug repositioning for psychiatric and neurological disorders through a network medicine approach

Abstract: Psychiatric and neurological disorders (PNDs) affect millions worldwide and only a few drugs achieve complete therapeutic success in the treatment of these disorders. Due to the high cost of developing novel drugs, drug repositioning represents a promising alternative method of treatment. In this manuscript, we used a network medicine approach to investigate the molecular characteristics of PNDs and identify novel drug candidates for repositioning. Using IBM Watson for Drug Discovery, a powerful machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 77 publications
(91 reference statements)
0
24
0
Order By: Relevance
“…When two diseases share a genetic mechanism, they can also present common clinical or epidemiological characteristics, despite having distinct etiological backgrounds (Barabási et al, 2011). These similarities can inform researchers of potential treatment options (Lüscher Dias et al, 2020). Here, we showed that diseases from inflammatory, psychiatric, and infectious etiologies significantly share genes with each other.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…When two diseases share a genetic mechanism, they can also present common clinical or epidemiological characteristics, despite having distinct etiological backgrounds (Barabási et al, 2011). These similarities can inform researchers of potential treatment options (Lüscher Dias et al, 2020). Here, we showed that diseases from inflammatory, psychiatric, and infectious etiologies significantly share genes with each other.…”
Section: Discussionmentioning
confidence: 69%
“…Recently, machine learning approaches have been used to analyze and integrate a variety of biological and medical data (Littmann et al, 2020;Zitnik et al, 2019). These include methods that integrate electronic health records (Rajkomar et al, 2018), capture latent knowledge from the material science literature (Tshitoyan et al, 2019), and discover potential novel drugs to treat psychiatric and neurological disorders using cognitive computing and network medicine analysis of the medical literature (Lüscher Dias et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, machine learning text-mining bibliometric approaches have been used to analyze and integrate a variety of biological, medical, and environmental science data (Littmann et al, 2020;Tan et al, 2021;Zitnik et al, 2019). These include methods that integrate electronic health records (Rajkomar et al, 2018), capture latent knowledge from the material science literature (Tshitoyan et al, 2019), investigate the evolution of research in environmental sciences (Tan et al, 2021), and discover potential novel drugs to treat psychiatric and neurological disorders using cognitive computing and network medicine analysis of the medical literature (Lu ¨scher Dias et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, in vitro models of high predictability and databases of results from transcriptomic analysis promise to increase the effectiveness and accuracy of this method. 2 Epilepsy is now well recognized as a symptom of many underlying causes, more accurately now referred to as the epilepsies. Recognizing the cause, often the result of a genetic mutation, has resulted in increasing recognition for targeting drug repositioning within the central nervous system, while endocrine and metabolic disorders represent relatively common sources of further repositioned therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%